Innominate Artery Compression Syndrome - Donuru, Achala; Kandula, Vinay; Madueme, Peace (AORTA, 2022)
Vascular mediated airway compromise is a fairly common clinical scenario. The diagnosis of innominate artery compression may be challenging due to lack of standardized imaging criteria for diagnosis or for surgical intervention.
Keywords: innominate artery; trachea; compression